Kontribusi Mangrove Pasar Ngalam Terhadap Pendapatan Masyarakat Nelayan - Rahmayani, Feby; Susatya, Agus; Senoaji, Gunggung; Wiryono; Uker, Damres (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
Mangrove forests are one of the forests that have been damaged. Human activities on the coast often ignore the preservation of mangrove forests. Coastal and marine areas of Indonesia have the highest biodiversity in the world (mega biodiversity). The research method used is a descriptive method, namely a method that focuses on solving actual problems that exist today. Solving actual problems is carried out through stages of activities including; data collection, compiling, analyzing, interpreting and making conclusions. Based on the results of the analysis, it can be seen that the capture fisheries business carried out by fishermen can optimally improve the standard of living of fishermen, which is carried out through efforts to increase production and productivity with the support of government policies in the fisheries sector. In order to increase the contribution of income from fisheries businesses run by fishermen, it can be done by implementing efforts to increase productivity supported by improving the quality of results. Thus, the goal of national development to improve the welfare of fishermen can be achieved.